Cancer patterns in nasopharyngeal carcinoma multiplex families over 15 years - Yu, Kelly J.; Hsu, Wan‐Lun; Chiang, Chun‐Ju; Chen, Tseng‐Cheng; Liu, Zhiwei; Lou, Pei‐Jen; Diehl, Scott; Goldstein, Alisa M.; Chen, Chien‐Jen; Wang, Cheng‐Ping; Hildesheim, Allan (Cancer, 2021)
Background Genetic and environmental factors are important determinants of nasopharyngeal carcinoma (NPC). NPC is associated with Epstein‐Barr virus (EBV) infection. Studies have reported familial aggregation of NPC, but evidence has been mixed for elevated rates of cancers other than NPC. Methods The authors reassessed their previous evaluation of familial aggregation of cancer in 348 high‐risk Taiwanese multiplex families with 2 or more NPC cases enrolled between 1980 and 2003. Participants were linked to the Taiwan National Cancer Registry and National Death Registry to identify cancers. Results In all, 2590 individuals contributed 37,959 person‐years over an average of 15 years of follow‐up; 314 incident cancers were identified. The authors computed multiple primary standardized incidence ratios (MP‐SIRs) to evaluate the overall risk and the risk of infection‐associated, EBV‐associated, and individual cancers. The overall MP‐SIR was 1.24 (95% confidence interval [CI], 1.10‐1.38). The exclusion of excess NPC risk led to an overall MP‐SIR of 1.11 (95% CI, 0.98‐1.25). Similarly, the risk of cancers associated with infectious agents was driven by the excess in NPC, and its exclusion led to an MP‐SIR of 1.22 (95% CI, 0.99‐1.48) for infection‐associated cancers and to an MP‐SIR of 1.18 (95% CI, 0.72‐1.82) for EBV‐associated cancers. The authors observed a significant excess of second cancers among NPC cases (oral cancer, mouth cancer, tongue cancer, gum cancer, nasal cavity cancer, bone cancer, and non‐Hodgkin lymphoma). Conclusions This reassessment of the largest NPC multiplex family study confirms the presence of NPC coaggregation within families in Taiwan but does not provide evidence for a broader familial syndrome involving NPC and other tumors. Among NPC cases, elevated rates of secondary cancers, mostly at the, head and neck and hematopoietic cancers suggest radiation treatment effects on subsequent cancer risk. This reassessment of the largest nasopharyngeal carcinoma (NPC) multiplex family study confirms the presence of NPC coaggregation within families in Taiwan but does not provide evidence for a broader familial syndrome involving NPC and other tumors. Among NPC cases, elevated rates of secondary cancers, mostly at the, head and neck and hematopoietic cancers suggest radiation treatment effects on subsequent cancer risk.